Persuasive Strategies in counsels’ closing arguments: A case study of Ghana’s 2012 Presidential election Petition - Ahialey, Helen Omavuayenor (University of Cape Coast, 2022)
Studies on courtroom discourse reveal that paramount on the agenda of lawyers is their desire to win cases. They try to persuade Justices to believe their side of an argument as against that of their opponent. Mobilising the combined forces of linguistic, appraisal and rhetorical resources, Counsels at the Supreme Court Hearing of Ghana’s 2012 Presidential Election Petition vehemently attempted to persuade the trial Justices to give a favourable judgement on behalf of their clients. This thesis, therefore, explored the language and appraisal resources employed by the Counsels for the Petitioners (The New Patriotic Party – NPP) and the 3rd Respondent (The National Democratic Congress – NDC) in their closing arguments, and how they utilised the Aristotelian rhetorical triad in their bid to persuade the trial Justices. Rooted in the qualitative research design, the study was anchored on Aristotle’s Three Species of Oratory and Perelman and Olbrechts-Tyteca’s The New Rhetoric. The method of analysis adopted for this study was Aristotelian Rhetorical Triangle, complemented by Joliffe’s Rhetorical Framework and Martin and White’s (2005) Appraisal Framework. The findings revealed that in an attempt to persuade the judges to give a favourable judgement on behalf of their clients, the Counsels appealed to the judges’ rationality and emotions. They also tried to construct a positive identity of themselves while they created an identity of otherness and negativity for their opponents. The study also revealed that the Counsels deployed dialogic contraction of deny and counter in order to disassociate themselves from the propositions of their opponents; while they shied away from proclaim and expand resources, perhaps for fear of conceding some shortcomings. Besides contributing to academia, the findings of the research are valuable to legal education in Ghana and beyond
xv,305p;,ill
Keywords: Argumentation Closing argument Election petition Persuasion Rhetoric